Admission sodium level and prognosis in adult Guillain-Barré syndrome - Sipilä JO; Kauko T; Soilu-Hänninen M. (Taylor & Francis, 2022)
PURPOSE:
Guillain-Barré syndrome (GBS) varies in severity and outcome. Hyponatremia predicts poor outcome but previous studies have used divergent methodology and (pseudo)hyponatremia caused by intravenous immunoglobulin administration may confound analysis. We studied if the plasma sodium level at admission was associated with GBS outcome.
METHODS:
All 69 patients at least 16 years of age treated for GBS in Turku University Hospital in 2004-2013 were included in the study. Clinical information was obtained from patient charts.
RESULTS:
Women had lower sodium levels at admission (138; IQR 135, 140) compared to men (140; IQR 138, 142; p = 0.0116) but no association of sodium levels with demographics, pre-hospital variables or basic GBS characteristics was found. Multivariate analyses showed lower admission sodium levels to be associated with worse functional status at one year from disease onset (OR 1.37; 95% CI 1.07-1.76; p = 0.0136) and probability of being discharged to another care facility from the hospital (OR 1.31; 95% CI 1.05-1.64; p = 0.0180) but not associated with need of intensive care unit care (p = 0.09) or mechanical ventilation (p = 0.45), length of hospital stay (p =0.48) or functional status at six months (p = 0.07).
CONCLUSIONS:
Low plasma sodium level at admission is associated with a more severe disease course and a worse outcome in GBS independently of previously identified prognostic factors. Hyponatremia does not, however, appear to be caused by disease-specific factors.